Innovative solution : unveiling the role of blockchain technology in green supply chain management : expert insights - Lorenzen, Lina Perette (2024)
This thesis examines the potential of blockchain technology (BCT) in green supply chain management (GSCM) and how it can be implemented. It investigates the capabilities of BCT to overcome existing barriers in GSCM and improve its environmental performance (EP), thereby closing the current research gap. A qualitative research method was used to answer the research question (RQ). Thirteen semi-structured expert interviews were conducted and analyzed using Kuckartz's content structuring method to gain deep insights into the potential of BCT in GSCM. The results of the qualitative research shed new light on the drivers and barriers of GSCM identified in the literature. Additionally, the findings highlight the potential of BCT in GSCM as an enabler to overcome GSCM barriers, particularly in enhancing trust, fostering collaboration and improving data transparency between supply chain (SC) participants. This facilitates more efficient implementation and monitoring of environmental initiatives throughout the SC and ultimately leads to a positive EP. Furthermore, the findings of this thesis provide practical insights for companies interested in integrating BCT into their GSCM practices. It offers guidance on how to design the blockchain architecture. Additionally, this thesis gives an overview of the necessary technological and organizational requirements for a successful implementation. Finally, it addresses critical aspects of BCT, such as energy consumption and vulnerability to data manipulation, to provide clarity on these concerns.